It could happen to you, representation of women and men in news reports of rape as seen in the English tabloid People's Journal (1993 and 2000) a comparative study - Saya-ao, Grelyn; lapuz, Rosalie
This study built on a strong belief in the interconnectedness of language, media, and society, is a comparison of the representation of women and men in news reports of rape as seen in the People's Journal in 1993 and in 2000. The researchers studied the headlines and the local paragraphs using naming analysis and transitivity analysis. Naming analysis shows how language is used to promote a particular attitude or to conform to an existing stereotype in the representations of women and men. Transitivity analysis, on the other hand, shows how women and menare regarded in society as revealed by the roles assigned to them. The study sheds light on how the position of women in society is both recreated and represented by the media through language. The shows how the gender roles of women and the value ascribed to them can be seem both in language and in society. it also shows how the media , being agent, could present their version of reality that the other institutions could either deny or validate.